Assessing Hotel Guests’ Satisfaction: The Influence of Hotel Image, Trust and Green Practices in Malaysia - Nurul Athirah Ikri; Nurzulida Abdul Hafiz; Norazlina Rahmat; Norzaidah Ngali; Assanova Marina (Information Management and Business Review, 2025)
This study examines the correlations between satisfaction and key factors such as brand image, trust, and green practices among hotel guests in Malaysia. As environmental awareness grows among consumers, many hotels have adopted green practices to meet the evolving expectations of environmentally conscious travelers. A survey was conducted with 386 Malaysian respondents aged 18 and above, all with prior experience visiting hotels that implemented green practices. Data was collected using convenience sampling through a structured Google Forms survey comprising three sections and a qualifying question about the respondents' experience with green hotels.  The findings reveal a positive correlation between guest satisfaction and the variables of green practices, trust, and hotel image. This study underscores the importance of integrating sustainable practices into hotel operations not only to enhance brand image but also to build trust with guests, thereby fostering long-term customer satisfaction and loyalty. The results provide valuable insights for hotel managers seeking to improve service quality and establish a competitive edge in the growing green tourism market.